Simulação fluidodinâmica da misturação de correntes líquidas aplicada à injeção de inibidores termodinâmicos de hidratos de gás - Valim, Leandro Saraiva (2018)
Natural gas hydrates are crystalline compounds formed by low molecular weight hydrocarbons and water in proper temperature and pressure conditions. In oil industry, one of the most likely scenarios of hydrate blockage appearance is the well shut in. When there is risk, a usual operational procedure is the replacement of flowline content by diesel or dead oil. However, there are scenarios where this procedure may not be the best option and the usage of thermodynamic hydrate inhibitor controlled injection may be the practicable solution. Therefore, this work aimed to understanding the mixing phenomenon between thermodynamic inhibitor and water through experimental data generation and modeling with subsequent algorithm implementation in OpenFOAM, a CFD software. The experimental results showed that in spite of ethanol and MEG being infinitely miscible in water, the mixing of these two inhibitors has completely different behavior. The implemented algorithm was capable to reproduce qualitatively the phenomena observed during experiments. What is more, the diffusive term seems not have relevance in macro-mixing process.